Kinerja Pengawasan DPRD terhadap Kebijakan Bupati Sinjai - Suardi Mukhlis; Yudarti Nur; Abdul Ganie Gaffar; Muhammad Suyuti (Journal of Government Insight, 2022)
This papers aims to analyze how the supervisory function of the Sinjai Regency DPRD is carried out regarding the policies of the Sinjai Regent and what obstacles are faced by the Sinjai Regency DPRD in implementing the supervisory function of the Sinjai Regent's policies. The research method used in this study is a qualitative descriptive method. The results of the study show that the implementation of the supervisory function of the Sinjai Regency DPRD has not implemented a systematic oversight mechanism, meaning that even though the supervision carried out by each commission is scheduled by the secretariat of the council, not most of the monitoring results are not followed up according to the mechanism in the DPRD. Hearings or hearings, official work visits or inspections as well as public complaints have not been prepared in a systematic pattern of activities, meaning which steps take precedence when following up on existing